2023
DOI: 10.22541/au.169945445.50394320/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The global influence of the IUCN Red List can hinder species conservation efforts

Ruben Dario Palacio,
María Abarca,
Dolors Armenteras
et al.

Abstract: The IUCN Red List of Threatened Species is an extinction risk assessment tool that has guided species conservation over the last five decades. However, as wildlife scientists and conservationists, we argue that its influence on the global conservation agenda can hinder effective species conservation efforts. Here, we review the limitations of the Red List and its misuse in priority setting, which can overlook local and regional contexts. This can result in improper allocation of conservation resources, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 128 publications
0
5
0
Order By: Relevance
“…These sources provide initial baseline information in certain cases, highlighting important areas for the protection of threatened and endemic species such as the northwestern, north‐eastern and south‐western Andean forest systems that are rich in species threatened by extinction, due in part to high levels of endemism observed in cloud forests (Mariscal et al., 2022; Tobar‐Suárez et al., 2022; Vandegrift et al., 2023). However, it is important to acknowledge that there is still uncertainty at the site‐specific level due to inherent biases associated with underlying sampling efforts (Palacio et al., 2023). This issue is particularly significant in the southeastern El Condor Protected Forest, where scientific exploration has only recently begun due to past conflicts between Peru and Ecuador.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These sources provide initial baseline information in certain cases, highlighting important areas for the protection of threatened and endemic species such as the northwestern, north‐eastern and south‐western Andean forest systems that are rich in species threatened by extinction, due in part to high levels of endemism observed in cloud forests (Mariscal et al., 2022; Tobar‐Suárez et al., 2022; Vandegrift et al., 2023). However, it is important to acknowledge that there is still uncertainty at the site‐specific level due to inherent biases associated with underlying sampling efforts (Palacio et al., 2023). This issue is particularly significant in the southeastern El Condor Protected Forest, where scientific exploration has only recently begun due to past conflicts between Peru and Ecuador.…”
Section: Discussionmentioning
confidence: 99%
“…358 bird species) and the number of species at risk of extinction (>242 Andean forest systems that are rich in species threatened by extinction, due in part to high levels of endemism observed in cloud forests (Mariscal et al, 2022;Tobar-Suárez et al, 2022;Vandegrift et al, 2023). However, it is important to acknowledge that there is still uncertainty at the site-specific level due to inherent biases associated with underlying sampling efforts (Palacio et al, 2023). Improvements are needed in data acquisition, collection and monitoring.…”
Section: The Precautionary Principle and The Rights Of Naturementioning
confidence: 99%
“…For the Watchlist, the score for each species was evaluated using three parameters, the number of specimens imported per year, vulnerability according to FishBase, and the IUCN Red List conservation status [ 5 ], as both databases provide complementary information on fish vulnerability [ 50 ] and, despite potential shortcomings [ 51 , 52 ], these are the most reliable and consolidated information available for fish species. The median number of specimens traded was normalized, assigning a value of 100 to the species with the highest eight-year median trade volume.…”
Section: Methodsmentioning
confidence: 99%
“…Palacio et al [94] also showed that inaccuracies in the Aves Red List hampered rather than supported their conservation. Furthermore, they found that Red List specialist groups did not respond to feedback and needed more transparency, and the Red List rules and guidelines were either not followed or misused.…”
Section: Species Prioritisation For Amphibian Rbcsmentioning
confidence: 99%
“…At the same time, Gerber [174] introduced a resource allocation framework to facilitate transparent and efficient decision-making. However, setting priorities based on the assessment of threats can be subjective and often needs more adequate data [91][92][93][94]. These and other perspectives collectively present the need for a comprehensive and transparent decision-making process toward resource allocation for amphibian RBCs [161].…”
Section: Financial Support and Managementmentioning
confidence: 99%